Da’wah bi al-Rihlah: A methodological concept of da’wah based on travel and tourism - Ibnu FIkri (Jurnal Ilmu Dakwah, 2022)
Objective This article will examine methodological concepts of science of da'wah packed into travel and tourism activities. As it will emerge, da'wah bi al-rihlah is an emic term in Islam to describe da'wah method of traveling from one place to another.Method The method used in this research is qualitative with a phenomenological approach. While the data collected for review comes from journal articles, books, and cultural records from various sources that are appropriate to the research topic.Result The results of this study argue that the term al-rihlah in the context of da'wah can be one of the approaches or methods of da'wah which is carried out by Muslims as a practical effort to support the dissemination of Islamic teachings in society. The concept of da'wah bi al-rihlah which has a concrete meaning of the method of da'wah through travel shows that this activity is very identical to the concept of wisata religi (religious tourism). This then has a consequence of how to synchronize theory and practice in the field.Implication The methodological conception that has been formed in this study will support the theoretical and practical impact of da'wah scholarship which continue to require a development from various perspectives.Originality The study of da’wah bi al-rihlah will place its position as an answer to the dynamics of social change to harmonize the scope of other established da'wah methods, such as da'wah bi al-hal, da'wah bi al-lisan, da'wah bi al-qalam, etc.***Tujuan artikel ini akan mengkaji konsep metodologi ilmu dakwah yang dikemas dalam kegiatan perjalanan dan wisata. Seperti yang akan muncul, dakwah bi al-rihlah adalah istilah emic dalam Islam untuk menggambarkan metode dakwah bepergian dari satu tempat ke tempat lain.Metode metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan fenomenologi. Sedangkan data yang dikumpulkan untuk ditelaah berasal dari artikel jurnal, buku, dan catatan budaya dari berbagai sumber yang sesuai dengan topik penelitian.Hasil penelitian ini berpendapat bahwa istilah al-rihlah dalam konteks dakwah dapat menjadi salah satu pendekatan atau metode dakwah yang dilakukan umat Islam sebagai upaya praktis untuk mendukung penyebarluasan ajaran Islam. dalam masyarakat. Konsep dakwah bi al-rihlah yang memiliki arti konkrit tentang metode dakwah melalui perjalanan menunjukkan bahwa kegiatan ini sangat identik dengan konsep wisata religi (wisata religi). Hal ini kemudian membawa konsekuensi bagaimana mensinkronkan teori dan praktek di lapangan.Implikasi Konsepsi metodologis yang terbentuk dalam kajian ini akan mendukung dampak teoritis dan praktis keilmuan dakwah yang terus membutuhkan pengembangan dari berbagai perspektif.Orisinalitas Kajian dakwah bi al-rihlah akan menempatkan posisinya sebagai jawaban atas dinamika perubahan sosial untuk menyelaraskan ruang lingkup metode dakwah lain yang mapan, seperti dakwah bi al-hal, dakwah bi al-lisan, dakwah bi al-qalam, dll.